KIZ/GM114 Balances the NF-ĸB Signaling by Antagonizing the Association of TRAF2/6 With Their Upstream Adaptors - Sun, Jiawei; Yang, Qili; Liu, Enping; Chen, Dahua; Sun, Qinmiao (Frontiers in Cell and Developmental Biology, 2022)
NF-κB signaling is a pivotal regulator of the inflammatory response and it must be tightly controlled to avoid an excessive inflammatory response that may lead to human chronic inflammatory and autoimmune diseases. Thus, how NF-κB signaling is precisely controlled is a long-standing question in the field. TRAF family proteins function as key adaptors to mediate various receptor signaling pathways including NF-κB signaling. Here, we characterize KIZ/GM114 protein as a negative regulator balancing the NF-κB signaling. Mechanistically, KIZ/GM114 binds TRAF6/2 through targeting the TRAF domains to antagonize the TRAF6-IRAK1 association or the TRAF2-TRADD association, consequently reducing the IL-1β/LPS/TNFα-induced NF-κB activation. Importantly, upon dextran sulfate sodium treatment, Gm114 deficiency induces a strong inflammatory response and severe acute colitis in mice, subsequently resulting in low survival rate. Collectively, our study not only identifies KIZ/GM114 as a regulator balancing the NF-κB signaling, but it also implies a new strategy for limiting excessive inflammatory response.